Impact of Crisis Prevention Training on Student Confidence in Patient Encounters - Carlson, Sarah; Dresow, Ben; Murugappan, Meena; Sieling, Emma; Srnec, Jason; Levy, Allison; Westra, Ruth; Christensen, Raymond; Stratton, Tim (Journal of Student-Run Clinics, 2016)
Background: The Health of People Everywhere (HOPE) Clinic is a student-run free triage and urgent care clinic that has operated in a Duluth, Minnesota homeless shelter since 2008. More than 100 University of Minnesota medical and pharmacy students volunteer at the clinic annually. The unpredictable nature of clinical interactions have highlighted the need to better prepare students on preventing escalation of difficult patient situations to crises. Methods: HOPE Clinic student leaders developed a Crisis Prevention Training Module around the themes of drug-seeking behavior, suicidal ideation and sexual harassment. A didactic presentation was followed by role-playing scenarios utilizing Theater Arts students as patients. A pre-training email survey was sent out to all 120 medical students and 180 pharmacy students on campus to evaluate students’ confidence to handle difficult patients. Medical students (n=60) and pharmacy students (n=116) who volunteer at the free clinic then had the chance to participate in crisis prevention training through the school. A post-training survey was sent out to all medical and pharmacy students on campus to compare the change in student confidence among students who participated in the training and students who did not. Results: On the pre-training survey, 40% of medical students and 17% of pharmacy students reported receiving previous crisis-prevention training (p=0.023). ANOVA of post-training survey results revealed a significant increase in student confidence to prevent a crisis compared to the pre-training survey among pharmacy students (p=0.001), but not among medical students. Conclusions: Pharmacy students perceived that crisis-prevention training increased their confidence to prevent uncomfortable patient interactions from escalating to a crisis.